LA-ICP-MS Zircon U-Pb Ages, geochemical characteristics, and geological significance of the early cretaceous volcanic rocks in Haitangwan Town, Southern Hainan Island, China - Yihua Lin; Dingyong Liang; Qinmin Yuan; Zailong Hu; Zhaoying Lv; Changyan Lv (PLoS ONE, 2025)
The Lumuwang Formation in Hainan Island is a key stratum for analyzing Mesozoic tectonic evolution. However, its depositional age relies only on sporopollen evidence, lacks high-precision dating, and its age attribution remains controversial. Additionally, the origin, tectonic setting of its volcanic interlayers and their connection to regional magmatic activities are unclear, which greatly restricts the systematic understanding of Hainan Island’s Mesozoic paleogeography and geotectonic evolution. Targeting a newly discovered set of volcanic rocks hosted in the terrigenous clastic rocks of the Lumuwan Formation in Haitangwan Town, Sanya City, this study systematically conducted zircon U-Pb dating and geochemical analysis. The results show that the minimum age is 121 Ma, thereby accurately constraining the depositional age of the clastic rocks of the Lumuwan Formation to the Early Cretaceous. Geochemical characteristics indicate that the volcanic rocks belong to the high-K calc-alkaline to shoshonitic series. Their low Mg # values and high MF and DI values indicate that the magma underwent highly differentiated evolution. The rare earth element (REE: La-Lu) distribution shows significant enrichment of light rare earth elements (LREE: La-Eu) and strong fractionation between LREE and heavy rare earth elements (HREE: Gd-Lu). Trace elements are characterized by enrichment of large ion lithophile elements (LILE: Rb, Ba, and K) and depletion of high field strength elements (HFSE: Nb, Ta, and Ti), highlighting typical island arc magma attributes. The above geochemical characteristics of the volcanic rocks reveal that the study area was in a transitional tectonic environment from an island arc to back-arc extension during the Early Cretaceous. This provides key empirical evidence for the dynamic process of the transition from a continental margin arc to intracontinental extension around 121 Ma in the South China continental margin, further deepening the scientific understanding of Mesozoic crust-mantle interaction and basin-mountain coupling processes in Hainan Island.